PEMODELAN DINDING CANTILEVER PENAHAN TANAH MENGGUNAKAN SAP 2000 DENGAN MENGANALISA KUAT TEKAN TERHADAP VARIASI BEBAN (STUDI KASUS DI RUAS JALAN BALEROJO KALEGEN) - Jefrizal Sihombing; Yoga Satria I; Amelia Rosana Putri; Widya Utama (Prokons: Jurnal Teknik Sipil, 2020)
The modeling of retaining wall is adapted to the real conditions on Balerejo Kalegen Street. This wall modeling uses a Cantilever type wall which has a height of 550 cm and a width of 385 cm which is useful for calculating the minimum strength of a cantilever wall for retaining the soil on the Balerejo Kalegen road. In addition, this wall is modeled to have a width of 55 cm, a heel width of 130 cm, a foot width of 130 cm, the width of the next leg is 100 cm, with a wall that enters it is 50 cm and using evenly distributed load variations has been adjusted where the load used is the burden amounting to 11,138, 5.5, 0.3869 tons. When inputting data into SAP 2000 beforehand, calculations must be made related to the force that will affect the wall, then modeling the walls according to the Cantilever shape. After that, Cantilever wall that has been made can be calculated compressive strength and shear strength where the compressive strength of the front wall with an average of 175,154 tons m, the back with an average of 62,666 tons m, the average front heel 866,054 tons m , and the back heel averages 910,463 tons m. Keywords: Cantilever, Retaining Walls, SAP 2000.